Instrument Flying Handbook : ASA FAA-H-8083-15B. - (ASA), Federal Aviation Administration (FAA)/Aviation Supplies & Academics (FAA Handbooks Series., 2015)
This is the eBook (epub) edition of this title. This is the FAA's primary pilot resource for instrument flight rules (IFR) covering everything pertinent to operating an aircraft in instrument meteorological conditions (IMC) or without reference to outside visuals, relying solely on the information gleaned from the cockpit. Readers will find chapters on the national airspace system, the air traffic control system, human factors, aerodynamics, flight instruments, flight maneuvers for IFR operations, navigation, emergency operations, as well as helicopter operations and more. The material in this.